Funny Salafism: Reframing Orthodoxy for Global Engagement on Social Media - Nauval, Mukhammad Hubbab (DINIKA : Academic Journal of Islamic Studies, 2025)
This study examines the evolving dynamics of Salafi preaching, focusing on how humor has been integrated into da’wah through social media platforms. Using netnography as a methodology, the research investigates the humorous style of Shaykh Assim al-Hakeem, whose global popularity exemplifies a shift from traditional, rigid Salafi approaches to more dynamic, engaging, and relatable methods. By analyzing content from platforms like Twitter, YouTube, and Facebook, the study highlights how humor facilitates broader audience engagement and fosters “mediated intimacy” with followers. This approach transcends sectarian boundaries, attracting both Muslim and non-Muslim audiences while reshaping public perceptions of Salafi identity. However, critiques persist, as some view this adaptation as masking the doctrinal rigidity and conservative underpinnings of Salafi ideology. The findings contribute to discussions on the intersection of digital media, religious authority, and identity in the contemporary Islamic world, emphasizing how Salafism negotiates the challenges and opportunities of the digital age to maintain relevance in diverse socio-political contexts.